WORK STRESS AS A MEDIATOR OF WORKLOAD, WORK ENVIRONMENT, AND TURNOVER INTENTION IN GENERATION Z EMPLOYEES - Tirta Ramadhanis Erdiantami; Muhamad Yunanto (Universitas Gunadarma, 2025)
Turnover intention is the tendency of employees to leave their jobs voluntarily. This study aims to analyze the role of work stress in mediating workload and work environment on turnover intention in Generation Z employees in Jakarta. The sample in this study is Generation Z workers who have worked for at least 6 months in various business sectors in Jakarta, especially technology, creative, and banking. The results show that workload and work environment have a significant effect on work stress; Workload has a significant positive effect on turnover intention, while the work environment has a significant negative effect. Work stress has been proven to play a role as an intervening variable. The results of the study provide novelty about the phenomenon of generation, characteristics of Generation Z who are more sensitive to stress, workload and work environment. The main contribution of this research is to enrich research related to employees from Gen Z, provide a theoretical basis for who Gen Z is in the workplace and identify factors that influence Gen Z's job retention and loyalty, which are different from previous generations.